Employment of Disabled People in Russian Regions: Status, Differentiation, Factors - O. V. Kuchmaeva (Статистика и экономика, 2020)
Purpose of the research. Employment of disabled people can be considered as a kind of reserve of the labor potential of the population in the conditions of aging and reduction of the population of working age. The purpose of the article is to consider the regional differentiation of employment of disabled people, to identify factors that affect the level of their employment and typological groups of Russian regions depending on the situation in the field of employment of disabled people.Materials and methods. The article is based on data on official disability for 2012-2019 and employment of disabled people, reflected in the system of state statistical accounting, as well as sample surveys of Rosstat. In addition, we used data on employment of disabled people from the Federal register of disabled people, which is operated by the Pension Fund of Russia.The conclusions of the article are based on the results of statistical analysis of data using descriptive statistics methods, calculation of nonparametric criteria (Tau-b Kendall) to assess differences in the distributions of indicators that characterize the socio-economic status of disabled people, as well as cluster analysis to identify typological groups of regions in terms of the situation in the employment of disabled people.Results. More than half of Russian disabled people are over the age of 60 (58.9% at the beginning of 2020). Age structure of disabled people affects their employment. People with disabilities do not feel in demand in the labor market. The share of employed (working) disabled people in Russia is 14.9% (2019). The employment rate of disabled people in the regions varies significantly – from 7.2% to 29.2%. Moreover, in 75 Russian regions, the share of working disabled does not exceed 20% of their number. The result of a cluster analysis based on data describing the employment of disabled people in the context of Russian regions in 2019 was the division of 85 regions of Russia into 4 clusters. There is a certain correlation between variables such as the percentage of disabled people working and the percentage of disabled people in employment, and the level of poverty in the regions. The share of disabled people among all employed in the region is related to the level of wages in the region and the amount of disability pensions.Conclusion. The small size of the disability pension encourages the employment of disabled people. In regions where the level of poverty is relatively low, even with high wages, employment of disabled people is minimal, due to both higher levels of social guarantees and competition between disabled/non-disabled people for jobs.The calculations show that, if appropriate conditions are created, the share of employed persons with disabilities among all disabled people may increase, which will attract from 33.5 thousand employees to 611.5 thousand employees to the labor market. Increasing employment for people with disabilities is important for the well-being of people with disabilities, as well as for the state and society.